Vaccine‐induced immune thrombosis and thrombocytopenia syndrome following adenovirus‐vectored severe acute respiratory syndrome coronavirus 2 vaccination: a novel hypothesis regarding mechanisms and implications for future vaccine development. Issue 10 (18th October 2021) - Monagle, Paul; Ng, Ashley P; Linden, Matthew; Ignjatovic, Vera; Farley, Alison; Taoudi, Samir; Pasricha, Sant Rayn; Torresi, Joseph
Abstract: We hypothesize that thrombosis with thrombocytopenia syndrome recently described after administration of adenovirus‐vectored vaccines for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) occurs as a result of the unique properties of the adenovirus vectors, which can have widespread biodistribution throughout the body. The antigen is delivered to megakaryocyte cells, which act as part of the primary immune system and distribute the antigen within progeny platelets, also a key component of the immune system. The interaction of the antigen induces preformed antiplatelet factor 4 (PF4) antibodies to bind to PF4–heparan sulfate complexes in the absence of exogenous heparin, at sites where the heparan sulfate concentration in the vascular glycocalyx is optimal for complex formation, causing thrombosis and thrombocytopenia as observed clinically. This hypothesis is testable in cell culture and animal models, and potentially in vivo, and if proven correct has significant implications for vaccine development and our understanding of the links between the coagulation and immune systems. Abstract : We hypothesize that thrombosis with thrombocytopenia syndrome recently described after administration of adenovirus‐vectored vaccines for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) occurs as a result of the unique properties of the adenovirus vectors, which can have widespread biodistribution throughout the body. The antigen is delivered to megakaryocyte cells, which act as part of the primary immune system and distribute the antigen within progeny platelets, also a key component of the immune system. The interaction of the antigen induces preformed antiplatelet factor 4 (PF4) antibodies to bind to PF4–heparan sulfate complexes in the absence of exogenous heparin, at sites where the heparan sulfate concentration in the vascular glycocalyx is optimal for complex formation, causing thrombosis and thrombocytopenia as observed clinically.